Energy-Aware Ch Selection And Optimized Routing Algorithm In Wireless Sensor Networks Using Wmba And Qoga (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
WSN is widely used in different applications, such as smart grid, water municipals, and health care, for monitoring the health condition of a patient, etc. But, the major challenge of WSN is energy efficiency. Energy Efficient-based WSN has always been a research focus to improve its performance. Aiming at optimal energy utilization to improve life expectancy with guaranteed QoS, an optimal CH selection and optimal routing algorithm in WSN is proposed. The work has carried out the selection of the CH based on various factors, such as residual energy of the nodes, proximity, distance to the base station, cost, node degree, and node centrality or coverage, using the proposed WMBA. After that, an optimal path selection using QOGA is done between CH and BS based on various factors, such as distance, residual energy, and node degree, under the MKMA clustering process. The experiment shows that the proposed methodology achieves better life expectancy for the WSN by achieving an energy consumption of 975J for the entire round of 2000 and a PDR of 93.56%, and remains to be energy efficient compared to the existing state-of-art methods.